Texas A&M University : A Pictorial History, 1876-1996, Second Edition - Dethloff, Henry C. (Book collections on Project MUSE., 1996)
Celebrates the 120-year history of Texas A & M University, from its founding in 1876 through the construction of the George Bush Presidential Library. Features historical and contemporary photographs and highlights the school's military tradition.